Children's Caregiving to Elderly Parents Based on Baserap Culture In Christian Families of Toulour Sub-Ethnicity In Minahasa - Mercy W.K. Waney; Esther Heydemans; Max Ruindungan (International Journal of Education, Information Technology, and Others, 2023)
The purpose of this study is to describe and explain children's caregiving to elderly parents based on Baserap culture in Christian families of Toulour sub-ethnicity in Minahasa and analyze children's caregiving to elderly parents based on Baserap culture of Toulour sub-ethnicity in Minahasa based on Christian theological values to be applied to Christian families in general. The method used is a qualitative research method with an ethnographic approach. In the process, the researcher conducts extensive observations of Christian families involved in the Baserap culture, where the researcher will observe the behavior and investigate the meaning of the behavior of the Baserap culture actors. The researcher engages in the informants' life activities and then conducts interviews and observations. Ultimately, the researcher will analyze the behavior to get the meaning of the base rap culture actors. The results of this research study explain that caregiving in the Baserap tradition has cultural values such as respect, obligation, and devotion of children to their parents as well as Christian values, which state that children who provide caregiving to elderly parents are God's orders with the value of respect and obedience manifested by love, patience, perseverance, joy, gentleness and loyalty in carrying out caregiving to elderly parents